2011
DOI: 10.1177/0960327110396532
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Cassia fistula fruit extract on bromobenzene-induced nephrotoxicity in mice

Abstract: The efficacy of a crude hydro-alcoholic extract of Cassia fistula (golden shower tree) fruit to protect the kidney against bromobenzene-induced toxicity was studied. Negative control mice received normal saline; positive control mice were given 460 mg/kg of bromobenzene; Cassia fistula treated mice received 200, 400, 600 and 800 mg/kg of Cassia fistula fruit extract followed by 460 mg/kg bromobenzene (daily by oral gavage for 10 days). On the 11th day, the mice were sacrificed, blood samples were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
(33 reference statements)
1
7
0
Order By: Relevance
“…We found that GM administration causes histopathological lesions in kidney, like glomerular atrophy, cell fragments in the tubules and swollen epithelial cells in proximal and distal convoluted tubules. Histopathological results are in rapport with the previous studies (Kalantari et al, 2011). In addition, the protective effects of cinnamon and/or parsley oils were confirmed by histopathological studies of kidney which indicates considerable improvement in proximal and distal convoluted tubules and glomerular atrophy in pre-treated groups (Fig.…”
Section: Resultssupporting
confidence: 88%
“…We found that GM administration causes histopathological lesions in kidney, like glomerular atrophy, cell fragments in the tubules and swollen epithelial cells in proximal and distal convoluted tubules. Histopathological results are in rapport with the previous studies (Kalantari et al, 2011). In addition, the protective effects of cinnamon and/or parsley oils were confirmed by histopathological studies of kidney which indicates considerable improvement in proximal and distal convoluted tubules and glomerular atrophy in pre-treated groups (Fig.…”
Section: Resultssupporting
confidence: 88%
“…37 It may be assumed that renal tubular function is affected more by bromobenzene-induced toxicity than glomerular filtration. 5 In the present study, intragastric intubation of bromobenzene (alone) once instigated renal injury that was evidenced by the elevation of serum urea, uric acid and creatinine and depletion in urinary levels of urea, uric acid and creatinine. From the results, it can be observed that pre-treatment of W. somnifera for 8 days to bromobenzene treated rats was able to normalize the levels of serum urea, uric and uric acid thus restoring the renal function and this may be due to some of its active components like alkaloids, sitoinosides and steroidal lactones.…”
Section: Discussionmentioning
confidence: 99%
“…Catalase (CAT) was assayed according to the method of Sinha 18 and chromic acetate produced by the action of catalase on dichromate acetic reagent was measured spectrophotometrically at 610 nm. Glutathione peroxidase (GPx) was assayed by the method of Rotruk et al 19 based on the reaction between glutathione remaining after the action of GPx 5,5 0 -dithiobis-(2-nitrobenzoic acid) to form a complex that has maximum absorption at 412 nm. Glutathione-s-transferase or GST 20 was measured using 1-Chloro-2, 4-dinitrobenzene as substrate and reduced glutathione was evaluated by the method of Moron et al 21 Total protein was estimated using the method of Lowry's et al 22 using bovine serum albumin as standard.…”
Section: Evaluation Of Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Both extracts exhibited significant antioxidant activity in DPPH, Nitric oxide and Hydroxyl radical induced invitro assay methods. Both extracts showed Dose-Dependent protective effect against lipid peroxidation and free radical generation in liver and kidney homogenates 24,25 . Antioxidant activity of Cassia fistula Linn) flowers in alloxan induced diabetic rats 26 .…”
Section: Ayurvedic Medicine Usesmentioning
confidence: 99%